Memory Quilts and Hope Chests: Adult Learners Craft Counterstories in Their Community Museum - Gruen, Rachael; Killian Lund, Virginia (Journal of adolescent & adult literacy, 2020)
The authors describe how a community museum created and curated by adult education students acted as an innovative and student-centered model to support learners in developing and demonstrating their literacy skills and knowledges. Using a case study approach to document and analyze students' counterstories (i.e., stories that disrupt dominant narratives), the authors highlight the ways in which creating and curating a community museum leveraged adult students' expertise and opened opportunities for meaningful civic action through counterstorying. The authors aim to provide adult literacy educators with a concrete example of how an expansive understanding of literacy skills within their curriculum, including the literacies of making and design, can support students' development of relevant content literacies and workforce competencies, including researching, multimodal composing, speaking, and collaborating.